CoS2 Nanoparticles-Embedded N‑Doped Carbon Nanobox Derived from ZIF-67 for Electrocatalytic N2‑to-NH3 Fixation under Ambient Conditions - Wei, Peipei; Xie, Hongtao; Zhu, Xiaojuan; Zhao, Runbo; Ji, Lei; Tong, Xin; Luo, Yongsong; Cui, Guanwei; Wang, Zhiming; Sun, Xuping (ACS sustainable chemistry & engineering, 2020)
NH3 is an indispensable chemical with numerous applications; however, its large-scale synthesis highly relies on the industrial Haber–Bosch process, which is performed under harsh conditions (high temperature and pressure). The electrochemical N2 reduction reaction (NRR) provides an avenue to synthesize NH3 under ambient conditions, yet durable and high-efficiency catalysts are needed. Herein, we report that a CoS2 nanoparticles-embedded N-doped carbon nanobox derived from ZIF-67 works as an efficient NRR catalyst under mild conditions. This catalyst achieves a large NH3 yield of 17.45 μg h–1 mg–1 cat. and a high Faradaic efficiency of 4.6% at −0.15 V vs the reversible hydrogen electrode in 0.1 M HCl. Furthermore, high electrochemical stability is displayed by the as-prepared catalyst.